The neuropsychology of love: Mechanisms of love in the human brain - Putri, Audifa Swastriana; Fauziyah, Farah; Retnasari, Retni; Medina, Karima Nada; Hamidah, Annisaul; Nugraheni, Rizki Putri (Jurnal Psikologi Terapan dan Pendidikan, 2025)
Love is one of the most powerful positive emotions experienced by human beings. When caught up in love, individuals undergo neurochemical changes in brain regions such as the amygdala, hippocampus, and prefrontal cortex. These changes are triggered by increased blood flow, reflecting the complex interplay between love and brain activity. Accordingly, this study aims to explore how love influences brain function, the various types of love, and their respective impacts on individuals.  This will be explored through a literature review of previous studies on the types and characteristics of love, as well as the neural and hormonal activity associated with it. This study employed a systematic literature review approach, resulting in fifteen selected articles for synthesis. The findings indicate that types of love include romantic love, maternal love, filial love, unconditional love, and friendship. Moreover, the hormones involved in love include oxytocin, dopamine, and testosterone. The study also reveals that visual processing of a loved one's face engages complex brain mechanisms. Unique characteristics of love include sexual desire, emotional conflict, and attachment.